Cultura política do primeiro liberalismo constitucional. A adesão das câmaras no processo de autonomização do Brasil - Iara Lis Schiavinatto (Araucaria)
The article is about the work of municipal governments as autonomous political bodies in the Brazilian constitutional process in 1820-26. Emphasis is placed on the historiographical debate of which this research is part, and the specific meaning of the term adesão developed in the links between municipal government, localities, and the Vintista Cortes in Lisbon, and the court in Rio de Janeiro. This research thus recovers social memory and memories of the empire, of local social, ethnic and political tensions, and ways of celebrating the adesão political pact that simultaneously linked the foundation of independent Brazil and constitutional monarchic rule.